2019
DOI: 10.1002/ppap.201900142
|View full text |Cite
|
Sign up to set email alerts
|

Maskless atmospheric pressure PECVD of SiOx films on both planar and nonplanar surfaces using a flexible atmospheric microplasma generation device

Abstract: This paper presents the use of a simple‐arranged, low‐cost, and flexible atmospheric pressure microplasma generation device (μPGD) with controlled gas discharge to achieve maskless atmospheric plasma‐enhanced chemical vapor deposition (PECVD) of SiOx films on both planar and nonplanar surfaces. The μPGD is mainly composed of a copper–polyimide–copper sandwich structure with predefined microfluidic channels. Uniform microplasmas of different shapes and dimensions were generated in the open air. SiOx films were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Figure 13 shows a possible monomer decomposition reaction chain due to the electron collision. 50) The Si-O bond energy in HMDSO molecule is about 8.3 eV, which is higher than that of Si-C (about 4.5 eV) and C-H (about 3.5 eV). Therefore, the CH 3 side groups have a high probability of rupture due to collisions by electrons that have relatively low energy [Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Figure 13 shows a possible monomer decomposition reaction chain due to the electron collision. 50) The Si-O bond energy in HMDSO molecule is about 8.3 eV, which is higher than that of Si-C (about 4.5 eV) and C-H (about 3.5 eV). Therefore, the CH 3 side groups have a high probability of rupture due to collisions by electrons that have relatively low energy [Fig.…”
Section: Discussionmentioning
confidence: 88%
“…where a kj (1) and a kj (2) are the stoichiometric coefficients of species k, as they appear on the left-and right-hand sides of a reaction j, respectively. The reactions and their rate coefficient are given in Supplementary Information.…”
Section: Global Model Descriptionmentioning
confidence: 99%
“…Coated polymers are widely used flexible electronics, [1,2] food packaging, [3,4] microelectronic encapsulation, [5,6] and dielectric materials. [7][8][9] As shown by Wang and colleagues, [1][2][3][4][5][6][7][8][9] SiO x are the preferred coating material due to their optical properties, low gas permeability, microwave inertness, and environmental benignancy. Two methods currently used to gain the SiO x layer are thermal oxidation and plasma-enhanced chemical vapor…”
Section: Introductionmentioning
confidence: 99%
“…In [15], researchers used a printed circuit board (PCB) fabrication-based method to manufacture a flexible plasma source within 30 min and with a cost of less than 0.25 USD. With regard to applications, flexible DBD plasma sources have shown remarkable effects in their use in food preservation [16,17], biomedical therapy [18][19][20], and surface processing of materials [15,21]. In the field of food preservation, it is reported that the microbial load of Listeria monocytogenes, Escherichia coli O157:H7, and Salmonella typhimurium decreased rapidly in samples of pork, beef [16], and cheese [17] after treatment with flexible plasma sources, without changing their physicochemical qualities.…”
Section: Introductionmentioning
confidence: 99%